The expression of peroxisome proliferatoractivated Receptor-gamma (ppary) in Colorectal carcinoma in relation to Tumour-associated macrophages - Mohamad, Haidi (2012)
The relationship between inflammation and cancer has even been established for many cancers such as colorectal cancer, prostate cancer and pancreatic cancer. However, the role of inflammation differs in different types of tumours. This study aims to assess the presence of tumour-associated macrophages and their role in colorectal cancers using a simple grading scale devised by Klintrup et aL, to determine the expression of PPARy in colorectal cancer and to determine if there is any association between the two parameters. A total of 90 resection cases of colorectal cancer was selected from the archives of the Pathology Department of Hospital University Sains Malaysia, Kubang Kerian, Kelantan from 2002 to 2011. Cases with sufficient tissue material to represent the central areas and the invasive margins were selected based on the H&E stained slides. Assessment of macrophages at central areas and the invasive margins of each case was performed. Immunohistochemical staining for macrophages using CD68 antibody for macrophage counting and PPARy were also carried out at the central areas and the invasive margins of each case. The Klintrup grading scale was positive for all cases. Comparison between macrophage counts and clinicopathological parameters revealed that the presence of lymphovascular permeation was inversely associated with the density of macrophage infiltration at the invasive margin (p=0.016, Pearson chi-square). Trends of association were seen for lymphovascular permeation and macrophage counts at the central areas. PPARy expression at the invasive margin was associated with lower TNM stages (p=0.039, Pearson chi-square) and absence of distant metastases (p-0.018, Pearson chi-square). The expression of PPARy and absence of metastases at the central areas was also significant (p=0.011, Fisher’s exact test). Inverse trends of association were seen for Dukes’ stage and PPARy expression both at the central areas and invasive margins (p=0.09 and 0.090, Fisher’s exact test) respectively. Also, at the invasive margins, expression of PPARy was associated with high macrophage counts (p=0.039, Fisher’s exact test). In conclusion, this study has elucidated that high tumour-associated macrophage infiltration and expression of PPARy especially at the invasive margins of colorectal cancers are markers of indolent tumour behavior and better prognosis; which is in line with the findings of previous research done.